Pengaruh Literasi Keuangan, Penggunaan Shopee Paylater dan Life Style terhadap Perilaku Konsumtif Mahasiswa: - Putri, Adellia Lailatul; Priantilianingtiasari, Ruly (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted with the aim of knowing the effect of financial literacy, the use of shopee paylater and also life style on the consumptive behavior of students of the Faculty of Economics and Islamic Business, Sayyid Ali Rahmatullah State Islamic University Tulungagung. The type of approach used is quantitative, with an associative type of research. The research population is students of the Faculty of Economics and Islamic Business with a total of 5,358, while the sample used is 372. This study uses purposive sampling technique. The data used is primary data and the data collection technique uses a questionnaire. The variables used are independent variables in the form of financial literacy, the use of shopee paylater and also life style, while the dependent variable is consumptive behavior. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, it shows that financial literacy has a significant influence on student consumptive behavior, the use of shopee paylater has a significant influence on student consumptive behavior, and life style has a significant effect on student consumptive behavior. Keywords: financial literacy, the use of shopee paylater, life style, comsumptive behavior